CONSUMERISM OF LEISURE CLASS IN SINGAPORE IN KEVIN KWAN’S CRAZY RICH ASIANS: A SOCIOLOGICAL APPROACH - Setiadi, Agni Nurwidia; Daulay, Resneri (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2021)
This research entitled “Consumerism of Leisure Class in Singapore in Kevin Kwan’s Crazy Rich Asians: A Sociological Approach”. The purpose of this study is to analyze the leisure class reflected in Singapore in the novel Crazy Rich Asians. In addition, the aim of this research is to reveal the consumerism of leisure class in Crazy Rich Asians. This novel contains the aspect about the style of consumer in Singapore.The research uses qualitative method to analyze the data. This study uses the mimetic approach by M.H. Abrams and two main concepts of theory of leisure class by Thorstein Veblen, these are conspicuous leisure and conspicuous consumption. The research applies the data of Singaporeans leisure class in the book Understanding Singaporeans: Values, Lifestyle, Aspirations and Consumption Behaviours by Keng et al. This study also applies the concept of uniquely Singaporean mindset in the book entitled The Cult of the Luxury Brand: Inside Asia’s Love affair with Luxury by Chadha and Paul as a tool to analyze the consumerism of leisure class in the novel Crazy Rich Asians. In this study, the researcher finds two main results. First, this study indicates conspicuous leisure as a signal of leisure class in Crazy Rich Asians based on seven leisure activities of Singaporean. They are sports, social, self-improvement, various charity, travel, home, and other activities. Second, the study discovers the consumerism of leisure class in Crazy Rich Asians and uniquely Singaporean mindset as a main result of leisure class’ consumerism in Singapore reflected in Crazy Rich Asians.